Optimization of cellulase production by Enhydrobacter sp. ACCA2 and its application in biomass saccharification - Premalatha, Nagaiah; Gopal, Nellaiappan O.; Jose, Polpass Arul; Anandham, Rangasamy; Kwon, Soon-Wo (Frontiers in Microbiology, 2015)
Cellulase finds use in saccharification of lignocellulosic agroresidues to fermentable sugars which can be used for production of commercially important metabolites. This study reports endoglucanase (CMCase) production by Enhydrobacter sp. ACCA2. The CMCase activity of the strain ACCA2 was successively improved by optimization of range of physical and nutritional parameter in a set of non-statistical and statistical experiments. Initial non-statistical selection of carbon source, incubation time, temperature and pH resulted in 1.07 fold increase of CMCase activity. In a subsequent statistical method, response surface methodology, optimization of medium components such as carboxymethylcellulose, peptone, NaCl, MgSO4•7H2O, FeSO4•7H2O, K2HPO4 and (NH4)2SO4 yielded further increase up to 2.39 fold CMCase activity. The cellulolytic potential was evaluated in biomass saccharification with different plant materials and the results revealed that the enzyme produced by strain may have significant commercial values for industrial saccharification process. Moreover, this is the first report of cellulase production by an Enhydrobacter spp.